Circulating γ-Tocopherol Concentrations Are Inversely Associated with Antioxidant Exposures and Directly Associated with Systemic Oxidative Stress and Inflammation in Adults. Issue 9 (31st August 2018) - Abdulla, Kennadiid A; Um, Caroline Y; Gross, Myron D; Bostick, Roberd M
Abstract: Background: Although α- and γ-tocopherol are co-consumed antioxidants, circulating γ-tocopherol concentrations were paradoxically found to be inversely associated with total vitamin E intake and circulating α-tocopherol concentrations. There are limited data on this apparent paradox or on determinants of circulating γ-tocopherol concentrations. Objective: To help clarify possible determinants of circulating γ-tocopherol concentrations, we investigated associations of circulating γ-tocopherol concentrations with various dietary and lifestyle factors and biomarkers of oxidative stress and inflammation. Methods: We pooled cross-sectional data from 2 outpatient, adult, elective colonoscopy populations (pooled n  = 419) on whom extensive dietary, lifestyle, and medical information was collected, and the following plasma concentrations were measured: α- and γ-tocopherol (via HPLC), F2 -isoprostanes (FiPs; via gas chromatography–mass spectrometry), and high-sensitivity C-reactive protein (hsCRP; via latex-enhanced immunonephelometry). Multivariable general linear models were used to assess mean γ-tocopherol differences across quantiles of plasma antioxidant micronutrients, FiPs, and hsCRP; an oxidative balance score [OBS; a composite of anti- and pro-oxidant dietary and lifestyle exposures (a higher score indicates higher antioxidant relative to pro-oxidant exposures)]; and multiple dietary and lifestyle factors. Results: Adjusted for serum total cholesterol, mean γ-tocopherol concentrations among those in the highest relative to the lowest tertiles of circulating α-tocopherol and β-carotene, the OBS, and total calcium and dietary fiber intakes were 31.0% ( P  < 0.0001), 29.0% ( P  < 0.0001), 27.6% ( P  = 0.0001), 29.7% ( P  < 0.0001), and 18.6% ( P  = 0.008) lower, respectively. For those in the highest relative to the lowest tertiles of circulating FiPs and hsCRP, mean γ-tocopherol concentrations were 50% ( P  < 0.0001) and 39.0% ( P  < 0.0001) higher, respectively. Conclusions: These findings support the conclusion that circulating γ-tocopherol concentrations are inversely associated with antioxidant exposures and directly associated with systemic oxidative stress and inflammation in adults. Additional research on possible mechanisms underlying these findings and on whether circulating γ-tocopherol may serve as a biomarker of oxidative stress, inflammation, or both is needed.